Filosofía y exégesis en las Enéadas. Las alas del alma plotiniana en su lectura del Fedro platónico - Martino, Gabriel (2014)
“Philosophy and Exegesis in the Enneads. The Wings of the Plotinean Soul in his reading of Plato’s Phaedrus”. In the present paper, we examine the role exegesis plays in the philosophy of the Enneads and, in particular, the way in which Plotinus interprets Plato. With this purpose we analyze, in the first place, some revealing passages of Porphyrius’ Life of Plotinus in order to understand, on the one hand, how late Greek thinkers conceived the exegetic endeavour and, on the other hand, the way in which plotinian philosophy was considered by his contemporaries. In the second section of this work, we examine the treatise IV 8 of the Enneads and try to show some peculiar aspects of Plotinus’ exegetic procedure as well as of his reading of Plato’s Phaedrus.